Jailing is failing: psychiatry can help - Andrew Carroll; Adam Brett (BJPsych Bulletin)
There is accumulating evidence that imprisonment is expensive but does little to address the underlying drivers of offending. At the same time, it is now recognised that a large proportion of prisoners are diagnosable with significant psychiatric disorders. In this piece we explore the potential role of psychiatry in addressing the societal challenge of a failing prison system. We argue that core psychiatric skills of engaging in balanced, values-based thinking and implementing sound clinical processes can play an important role in reducing reoffending risk. We briefly discuss some of the key challenges involved and outline several relevant service models.